(3WHbGJ GdTGaYjI GdhSWis - (3CHh fUQ YHO GdhgGH Hf Ydj Hf YHO GdcGai JGL GdOjf GdSjci GdTGaYjs; (3JGL GdOjf GdSHcj , CHh fUQ,J (B771 (3g` s
(3ChdgG (B:s
(3jHJOF HJQLeI WGgQ Hf YHO Gddg GdEjdGai s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs